Production and Optimization of Pectinase from Pectinolytic Fungi Cultivated on Mango peels and Pectin Subjected to Submerged Fermentation - Kelemu Mulluye; Ameha Kebede; Negussie Bussa (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2021)
Pectinases are the group of enzymes that degrade pectin. This study was conducted with the aim of isolation of efficient pectinase producing pectinolytic fungi from the decomposing mango peels using extracted mango peels pectin as a growth substrate under submerged fermentation, determining optimum pectinase production conditions with regards to some physicochemical parameters. The organisms were screened for the production of pectinase using Pectin agar media, and the two active pectinolytic fungi (P1 and P2) were isolated. pectinase production media was later used for the Lab scale production of pectinase by inoculating p1 and p2 and incubating for 7 days. The enzyme was extracted after seven days of fermentation and every day tested for their pectinolytic activity. P2 showed relatively higher pectinolytic activity and was therefore used for further studies. P2 was inoculated into a broth containing mango pectin under submerged fermentation. Results indicate that a pectin yield of mango peel 17.75%. Different parameters optimization processes were investigated on submerged fermentation namely pH, incubation period, temperature and substrate concentration optima were found 6, 4 days, 35oC and 1.5% respectively. The result suggests that mango peels have high pectin content and can be used for the value-added synthesis of pectinase.